Weight Fluctuation and Diet Concern Negatively Affect Food-Related Life Satisfaction in Chilean Male and Female Adolescents - Schnettler, Berta; Miranda-Zapata, Edgardo; Grunert, Klaus G.; Lobos, Germán; Denegri, Marianela; Hueche, Clementina (Frontiers in Psychology, 2018)
Problematic eating behaviors and obesity are frequent problems encountered during adolescence that may potentially result in psychological, social and physical consequences that may interfere with adolescent development and well-being. The present study evaluates the relationship between satisfaction with food-related life and satisfaction with family life, and their relationship with life satisfaction in male and female adolescents. We explored the relationships between both subscales of the Revised Restraint Scale (RRS), Diet Concern (DC) and Weight Fluctuation (WF) and adolescent life satisfaction as well as satisfaction with food-related life and family life. We also explored the moderating role of socioeconomic status (SES). A questionnaire was applied to a non-probabilistic sample of 470 adolescents (mean age 13.2 years, 52.3% female) in Chile, including the RRS, Satisfaction with Life Scale (SWLS), Satisfaction with Food-related Life (SWL-Food) scale and Satisfaction with Family Life (SWL-Family) scale. Using structural equation modeling, we found that adolescent life satisfaction was related to satisfaction with family life and food-related life in both genders. In male adolescents, a negative relationship was identified between WF and food-related life satisfaction. In contrast, a negative relationship was identified in female adolescents between DC and food-related life satisfaction. DC and WF were not directly related to life satisfaction or to satisfaction with family life in either gender. SES was found to moderate the relationship between food-related life satisfaction and life satisfaction and the relationship between WF and food-related life satisfaction in female adolescents. These findings suggest that reducing diet concern in female adolescents and reducing weight fluctuation in male adolescents and female adolescents from higher SES may improve their food-related life satisfaction.